A Hepatitis C Virus NS5A Phosphorylation Site That Regulates RNA Replication - LeMay, K. L. (American Society for Microbiology, 2013)
The hepatitis C virus NS5A protein is essential for RNA replication and virion assembly. NS5A is phosphorylated on multiple residues during infections, but these sites remain uncharacterized. Here we identify serine 222 of genotype 2a NS5A as a phosphorylation site that functions as a negative regulator of RNA replication. This site is a component of the hyperphosphorylated form of NS5A, which is in good agreement with previous observations that hyperphosphorylation negatively affects replication.